Validation of performance assessment instrument on futsal game in extracurricular activities - Nugroho, Mahir Dwi; Tomoliyus, Tomoliyus (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2019)
The research is aimed at evaluating the content validity and performance of an assessment instrument, based on futsal games in extracurricular activities. This is very important because of its ability to review objectively and also the application as a material for coach evaluation. In addition, the method used was research evaluation, with documents as the subject, and Delphi technique was applied in data collection by 5 experts. Furthermore analysis involved the use of formula Content Validity Ratio (CVR), which was developed by Lawshe, and the results showed the values obtained to be above 0.05, with indicators of Decision Making being 1.00, Skill = 1.00, Support = 0. 60 and Re-position = 1.00. In conclusion, the performance assessment instrument based on futsal game in extracurricular activities was observed to have high value validity contents.